Determinants of Extra-role Behaviour of Lecturers in Islamic Higher Education - Hesi Eka Puteri; Anne Putri; Sandra Dewi (Tarbawi, 2021)
This study investigated the determinants of Extra-role behaviour of lecturers at state Islamic universities in Indonesia. This study was quantitative research conducted through a survey of several Islamic Higher Education in Indonesia in 2020. Data were collected using a questionnaire and analyzed using PLS-Regression (Partial Least Square - Regression) on 173 active lecturers. The finding revealed that 49.8% of the Extra-role of lecturer achievement variation could be explained by factors covering Talent management, Job involvement, Personality, and Grit. Job involvement and Personality were strong predictors of lecturer Extra-roles. This empirical finding offers empirical evidence of Extra-role behaviour in Islamic Higher Education by examining some previous predictors in business institutions. This study recommends further testing of the relationship between Grit and lecturer's Extra-roles in more comprehensive cases. This study recommends that apart from Talent management and Job involvement, to improve the Extra-role behaviour of lecturers, it is also necessary to pay attention to character building